Proceedings of the 43rd International ACM SIGIR Conference on Research and Development in Information Retrieval 2020
DOI: 10.1145/3397271.3401044
|View full text |Cite
|
Sign up to set email alerts
|

Table Search Using a Deep Contextualized Language Model

Abstract: Pretrained contextualized language models such as BERT have achieved impressive results on various natural language processing benchmarks. Benefiting from multiple pretraining tasks and large scale training corpora, pretrained models can capture complex syntactic word relations. In this paper, we use the deep contextualized language model BERT for the task of ad hoc table retrieval. We investigate how to encode table content considering the table structure and input length limit of BERT. We also propose an app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…We analyzed the cell adjacency of these tables and discovered that 1,886 of them came with nested layout structures involving merged cells. Following previous works [15,66], we run 5-fold cross-validation on this dataset. Baselines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed the cell adjacency of these tables and discovered that 1,886 of them came with nested layout structures involving merged cells. Following previous works [15,66], we run 5-fold cross-validation on this dataset. Baselines.…”
Section: Methodsmentioning
confidence: 99%
“…Sun et al [53] proposed query-specific attention mechanisms to aggregate table cell embeddings, which provided a flexible way to induce the relevance between a query and different parts of a table with softmax classifiers. Through this direction, Chen et al [15] designed an embedding-based feature selection technique to select most relevant content from cells, rows and columns of each table, where BERT [17] was used to encode the concatenated text sequence of selected table content. Chen et al [15] also observed that combining neural network methods and feature-based methods achieved further improvements.…”
Section: Natural Language Table Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al (2020) focused mainly on pretrained Transformers (Vaswani et al, 2017) for text ranking, where they showed that a BERT-based multi-stage ranking model is a potential choice for a tradeoff between effectiveness and efficiency of a neural ranking model. Xu et al (2020b) reviewed deep learning models for matching in document retrieval and recommendation systems. The authors grouped the neural ranking models into two categories which are representation learning and matching function learning.…”
Section: Introductionmentioning
confidence: 99%
“…The authors grouped the neural ranking models into two categories which are representation learning and matching function learning. Compared to the survey of Xu et al (2020b), in addition to grouping neural ranking models into five categories based on the neural components and design (Sect. 6), we summarize multiple models based on nine features that are frequently presented in the neural ranking models (Sect.…”
Section: Introductionmentioning
confidence: 99%